السلوك القیادي لدى الاطفال الایتام واقرانھم غیر الایتام في المرحلة الابتدائیة (Journal of the College of Education for Women, 2019)
The family is considered one of the most important social institutions which has astrong and clear effect on the child in forming his personality through the processof social upbringing which works on transforming the child from a merelybiological being into an individual who has customs and traditions and the behaviorof the group to which he belongs, and till now there is no social organization orinstitution that can do this process not even in partial way like the family.Therefore depriving the child of his parents leads to depriving him of the normalchances of growth which relate to his age stage and thus this shortcoming is hard totreat and based on the preceding the current research aimed at the following:((Knowing the level of the leadership behavior in the orphan pupils in comparisonto their normal peers))And the researcher concluded through the results of the research that the normalpupils have a leadership behavior more than the orphan pupils .Therefore theresearcher recommends urging the parents or who take their place to take care inthe development of the child's personality and providing the necessary safety andcare to the orphan child, and making symposiums with the cultural cautioning ofthe media aiming at directing the parents and who takes their place about how todeal with the orphan child.